English Teachers’ Role in the 21st Century Learning - Melvina Melvina; MHD Natsir; Yulmiati Yulmiati; Shinta Andilla (JETL (Journal of Education, Teaching and Learning), 2025)
The English teacher in the 21st-century era is demanded to be the technology expert, project manager, assessor, collaborator, facilitator, and lifelong learner. This study examines the English teachers’ beliefs regarding their roles as technology experts. A qualitative approach was employed to gather data from two English teachers from a vocational high school in Padang, West Sumatra. They were selected using a purposive sampling technique with categorization they are familiar with and use technology in their teaching practice. The data of the research are collected through interviews conducted with the use of audio recorders. The Technology Acceptance Model (TAM) theory is the foundation for this study’s conceptual framework. The findings indicated that English teachers believe they have played their role as technology experts. They have utilized technology in the teaching and learning process. It also found teachers have faith that technology is easy to use and provides much usefulness to support English language teaching. Furthermore, it was found that schools facilitate technology, but the amount of technology support available was still limited